Diabetes in pregnancy : its impact on Australian women and their babies - Australian Institute of Health and Welfare (Canberra : Australian Institute of Health and Welfare, 2010)
Annotation pending.
Bibliography (p. 157-159).
Also available in an electronic version via the Internet. Address as at 16/5/2011: http://www.aihw.gov.au/publications/cvd/52/11837.pdf
Keywords: Diabetes in pregnancy -- Australia -- Statistics; Diabetes -- Australia -- Statistics; Reproduction - Pregnancy; Health - Endocrine system - Diabetes; Health status - Womens health - Maternal health